Booster medication to achieve capsule excretion in colon capsule endoscopy: a randomized controlled trial of three regimens - Kroijer, Rasmus; Dyrvig, Anne-Kirstine; Kobaek-Larsen, Morten; Støvring, Jens Overgaard; Qvist, Niels; Baatrup, Gunnar (Endoscopy International Open, 2018)
Background and study aims To achieve a complete colon capsule endoscopy, the entire colon must be visualized, clean and filled with clear fluids. The primary aim was to compare three booster regimens in colon capsule endoscopy in achieving capsule excretion within recording time. Secondary aims were quality of bowel cleansing and completion rate (both adequate cleansing and capsule excretion).Patients and methods Patients scheduled for follow-up colonoscopy due to previous neoplastic findings or familial history of colorectal cancer aged 18 to 70 years were eligible. Bowel preparation was 2-L split doses of polyethylene glycol. Patients were randomized to three booster regimens of either polyethylene glycol (Group A), sulfate-based solution (Group B) or polyethylene glycol with iodine oral contrast (Group C). Results One hundred eighty participants were included and randomized into three groups of 60. Capsule excretion was 70 % (95 % CI: 58 – 80) in Group A, 73 % (95 % CI: 61 – 83) in Group B and in 68 % (95 % CI: 56 – 79) in Group C, no statistically significant differences. Bowel cleansing grade was statistically significant better in Group B compared to Group A (P = 0.03), but there were no statistically significant differences between Groups C and A (P = 0.40). Complete examination rate was 65 % (95 % CI: 53 – 77), 72 % (95 % CI: 61 – 83) and 62 % (95 % CI: 50 – 74) in Group A, B and C respectively, not statistically significant different.Conclusions Sulfate-based solution resulted in statistically significant better bowel cleansing compared to polyethylene glycol. Overall the excretion and completion rate was suboptimal. Achieving a high completion rate using patient-tolerable and low-risk compounds is still a challenge.